Votive Body Parts in Greek and Roman Religion - Jessica Hughes (Les Carnets de l’ACoSt)
This book examines a type of object that was widespread and very popular in classical antiquity - votive offerings in the shape of parts of the human body, using them to explore how beliefs about the body changed throughout the period.